Microscopic Colitis: A Clinical Case - E. V. Reznik; A. S. Smirnova; Y. Y. Gudilova; I. E. Baykova; G. N. Golukhov (SINAPS LLC, 2023)
Microscopic colitis is an inflammatory bowel disease of unknown etiology that presents as chronic watery diarrhea with no endoscopic evidence of the bowel involvement but with the microscopic changes. Diagnosis of microscopic colitis is based on the histological examination of the intestinal biopsy and requires a highly qualified gastroenterologist, endoscopist and histologist. The article presents a clinical case of microscopic colitis in a 42-year-old patient, reflects the main stages of diagnosis and treatment of the patient.